Modulation of the tumor microenvironment and inhibition of EGF/EGFR pathway: Novel anti‐tumor mechanisms of Cannabidiol in breast cancer. Issue 4 (19th January 2015) - Elbaz, Mohamad; Nasser, Mohd W.; Ravi, Janani; Wani, Nissar A.; Ahirwar, Dinesh K.; Zhao, Helong; Oghumu, Steve; Satoskar, Abhay R.; Shilo, Konstantin; Carson, William E.; Ganju, Ramesh K.
Abstract : The anti‐tumor role and mechanisms of Cannabidiol (CBD), a non‐psychotropic cannabinoid compound, are not well studied especially in triple‐negative breast cancer (TNBC). In the present study, we analyzed CBD's anti‐tumorigenic activity against highly aggressive breast cancer cell lines including TNBC subtype. We show here ‐for the first time‐that CBD significantly inhibits epidermal growth factor (EGF)‐induced proliferation and chemotaxis of breast cancer cells. Further studies revealed that CBD inhibits EGF‐induced activation of EGFR, ERK, AKT and NF‐kB signaling pathways as well as MMP2 and MMP9 secretion. In addition, we demonstrated that CBD inhibits tumor growth and metastasis in different mouse model systems. Analysis of molecular mechanisms revealed that CBD significantly inhibits the recruitment of tumor‐associated macrophages in primary tumor stroma and secondary lung metastases. Similarly, our in vitro studies showed a significant reduction in the number of migrated RAW 264.7 cells towards the conditioned medium of CBD‐treated cancer cells. The conditioned medium of CBD‐treated cancer cells also showed lower levels of GM‐CSF and CCL3 cytokines which are important for macrophage recruitment and activation. In summary, our study shows ‐for the first time‐that CBD inhibits breast cancer growth and metastasis through novel mechanisms by inhibiting EGF/EGFR signaling and modulating the tumor microenvironment. These results also indicate that CBD can be used as a novel therapeutic option to inhibit growth and metastasis of highly aggressive breast cancer subtypes including TNBC, which currently have limited therapeutic options and are associated with poor prognosis and low survival rates. Highlights: CBD inhibits TNBC proliferation, migration and invasion. CBD inhibits EGF/EGFR signaling pathway and its downstream targets. CBD inhibits GM‐CSF, CCL3 and MIP‐2 secretion from cancer cells. CBD inhibits breast cancer growth and metastasis in two mouse models. CBD inhibit M2 macrophage recruitment to the tumor stroma.